2000
DOI: 10.1200/jco.2000.18.8.1668
|View full text |Cite
|
Sign up to set email alerts
|

Outcome at 8 Years After Breast-Conserving Surgery and Radiation Therapy for Invasive Breast Cancer: Influence of Margin Status and Systemic Therapy on Local Recurrence

Abstract: Pathologic margin status and the use of adjuvant systemic therapy are the most important factors associated with LR among patients treated with breast-conserving surgery and radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
242
4
9

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(267 citation statements)
references
References 23 publications
12
242
4
9
Order By: Relevance
“…[3][4][5][6] Ideally, the tumour, along with a margin of at least 10 mm of normalappearing tissue, is resected to attempt to remove any microscopic cancer. The minimum cosmetically acceptable tumour-free margin in relation to the risk of local or distant recurrence has been debated in many studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Ideally, the tumour, along with a margin of at least 10 mm of normalappearing tissue, is resected to attempt to remove any microscopic cancer. The minimum cosmetically acceptable tumour-free margin in relation to the risk of local or distant recurrence has been debated in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…2 Local recurrence after conservation surgery usually results from growth of residual cancer adjacent to the excised primary tumour or from multicentric disease. [3][4][5][6] Complete local excision, confirmed histologically, is essential to ensure that the risk of local recurrence is minimal. It is now recognised that for patients with multicentric disease detected prior to surgery, breast conservation surgery may still be appropriate if all clinically and radiologically apparent abnormalities are removed, clear margins of resection are achieved, and there is no extensive intraductal component present.…”
Section: Clinical and Surgical Management Of Early Breast Cancermentioning
confidence: 99%
“…Horiguchi et al, 1999). No difference between positive and negative margins was found in the 1 mm margin study but the numbers were small (Assersohn et al,, tege Park et al, 2000) and the third study demonstrated increased local recurrence for diffusely positive versus any other margin (Schnitt et aL,1994). Two of these studies also compared focally positive versus negative margins.…”
Section: Qualitv Assessmentmentioning
confidence: 99%
“…Based on the Milan quadrantectomy data, Veronesi also reported ahazard ratio for distant disease of 4.62 in patients with local rectrrence (Veronesi et al, 1995). Decreased (Fortin, Larochelle, Laverdiere, Lavertu, & Tremblay, 1999 (Borger et al, 1994;Park et al, 2000) and the presence of DCIS (Borger et a1.,1994; Luu, Otis, Reed, Garb, & Frank, 1999;Tartter et al', 2000). (Holland, Veling, Mravunac, & Hendriks, 1985).…”
Section: Breast Conserving Therapv Versus Mastectomymentioning
confidence: 99%
See 1 more Smart Citation